Multi-threadaed unbalanced power flow of large-scale networks with advanced bus classification. (July 2022) - Vojnović, Nikola; Vidaković, Jovana; Vidaković, Milan
Highlights: Power flow calculation of large-scale networks has been changed due to the incorporation of electronically coupled energy resources. Traditional single-threaded solutions have existed for long time for balanced large-scale networks. Multi-threaded implementation offers significant speedup in power flow calculation. The advanced bus type classification has been introduced in order to model more accurate control strategies of electronically coupled energy resources. Abstract: The multi-threaded implementations of the power flow calculation procedures became more and more popular as they decreased calculation speeds. The multi-threaded power flow calculation with the integration of the control strategies of traditional and electronically coupled energy resources in asymmetrical states are the main subject of this paper and the main objectives are as follows: (i) to present the models of traditional and electronically coupled energy resources and to incorporate their control strategies into more accurate bus type classification, and develop the unbalanced power-flow calculation procedure, (ii) to identify which parts of the proposed algorithm could be implemented in the multi-threaded manner, (iii) based on the measured performance data, to further optimize the identified parts of the algorithm using subthreads, and (iv) to develop the multi-threaded power flow procedure for unbalanced large-scale weakly-meshed and meshed networks. These procedures were successfully tested on large-scale unbalanced weakly-meshed and meshed networks. Graphical Abstract: Image, graphical abstract .